Study on surface deformation pattern in mine closure area of complex karst mountainous region based on SBAS-InSAR technology - Huang, Guangcai; Dong, Jihong; Xi, Wenfei; Zhao, Zilong; Li, Sifa; Kuang, Zhong; An, Quan; Wei, Jin; Zhu, Yuhua (Frontiers in Earth Science, 2024)
Liupanshui City in Guizhou Province represents a karst mountainous region with a delicate geological environment. The area has a long history of coal mining, and several coal mines have been progressively closed in recent years. However, even after closure of coal mines, the fractured rock mass in the mined-out areas continues to undergo deformation over a specific period. In karst mountainous regions, this deformation is affected by various factors including elevation, slope, precipitation, and vegetation. In this study, we employed SBAS-InSAR technology to construct a time series of surface deformation data from January 2019 to May 2022 within Liupanshui City's LuJiaZhai-DaPingDi Minefield. Subsequently, this data was comprehensively analyzed in conjunction with time series vegetation cover, monthly precipitation, elevation, and slope data from the identical period. The key findings of this research are as follows: (1) After the closure of the mine, the subsidence area gradually stabilized, yet the volume of subsidence continues to increase. The subsidence area primarily occurs near the MaiZiGou Coal Mine air-mining area, which had a relatively short closure time, as well as in higher elevation areas in the southern and eastern parts of the minefield. Specifically, the maximum cumulative subsidence and the subsidence rate during the study period reached -60.3mm and -21.83mm/a, respectively. (2) Surface deformation is closely linked to slope, vegetation type, and rainfall, with subsidence rates and amounts noticeably higher during the rainy season than in the dry season. (3) Surface vegetation cover types display varied effects on deformation, with grassland or shrub areas being more sensitive to precipitation than forests. Forests, especially pine and fir, show a delayed subsidence response to rain, typically 2-3 months post-rainy season onset. This inhibitory effect lessens with increasing slope, particularly beyond a 25°threshold, where responsiveness to precipitation and associated subsidence significantly increase. The findings of this study hold substantial scientific implications for the restoration and management of closed mining areas, as well as the prevention of geological hazards in karst complex mountainous regions.